Effects of enteral nutrition in stroke: an updated review - Jiang, Dailiang; Nie, Lei; Xiang, Xuying; Guo, Xiaoqing; Qin, Mengting; Wang, Shengnan; Chen, Jiaojiao; Feng, Yuhang; Huang, Ming; Mao, Ling (Frontiers in Nutrition, 2025)
Stroke is a leading cause of death and functional decline that places a significant burden on healthcare systems. Malnutrition is a critical clinical concern that complicates the condition of stroke patients and contributes to unfavorable outcomes. Dysphagia is the primary cause of malnutrition in the acute stage after stroke. Enteral nutrition (EN) has been employed to manage the nutritional status of stroke patients to prevent and treat malnutrition. Early EN (EEN) has been shown to reduce mortality and the prevalence of malnutrition while enhancing functional outcomes. In the majority of cases requiring nutritional support, nasogastric tube (NGT) placement is prioritized. However, under specific circumstances, direct enteral tube (DET) feeding that includes percutaneous endoscopic gastrostomy (PEG) and percutaneous endoscopic jejunostomy (PEJ), offers distinct advantages, particularly for PEG. Compared to intermittent EN, continuous EN demonstrates better tolerance. An EN protocol providing sufficient nutrient supply and energy support can alleviate neurological deficits and reduce the severity of motor dysfunction in stroke patients, thereby improving their prognosis. Energy-rich formulations of EN and EEN may be associated with a lower incidence of stroke-associated pneumonia (SAP). However, the use of EN may lead to an increased incidence of digestive complications, and hyperglycemia. In this study, we reviewed the indications, opportunities, and management methods for EN application, along with the nutrient composition of nutritional protocols for stroke patients.